Drones for litter monitoring on coasts and rivers: suitable flight altitude and image resolution - Andriolo, Umberto; Topouzelis, Konstantinos; van Emmerik, Tim H M; Papakonstantinou, Apostolos; Monteiro, João Gama; Isobe, Atsuhiko; Hidaka, Mitsuko; Kako, Shin'ichiro; Kataoka, Tomoya; Gonçalves, Gil (My University, 2023)
Multirotor drones can be efficiently used to monitor macro-litter in coastal and riverine environments. Litter on beaches, dunes and riverbanks, along with floating litter on coastal and river waters, can be spotted and mapped from aerial drone images. Items detection and classification are prone to image resolution, which is expressed in terms of Ground Sampling Distance (GSD). The GSD is determined by drone flight altitude and camera properties. This paper investigates what is a suitable GSD value for litter survey. Drone flight altitude and camera setup should be chosen to obtain a GSD between 0.5 cm/px and 1.25 cm/px. Within this range, the lowest GSD allows litter categorization and classification, whereas the highest value should be adopted for a coarser litter census. In the vision of drawing up a global protocol for drone-based litter surveys, this work sets the ground for homogenizing data collection and litter assessments.
Keywords: Environmental pollution; Ground Sampling Distance; Plastic; Remote sensing; UAV